A Narrative Review of the Coronavirus Disease 2019 Response in the Kingdom of Bahrain - Manaf AlQahtani, MD, FRCPC, FRCPI; Jaleela Sayed Jawad, MD, MSc; Abdulla AlAwadhi, MSc; Basma Mahmood Al Saffar, MD, MSc; Ejlal Faisal AlAlawi, MD, MSc; Hashim Hadi Sayed Adnan, MPH; Hammam Haridy, MD; Jean Joury, BSPharm, CMD; Graciela del Carmen Morales, MD (Elsevier, 2024)
ABSTRACT: Background: The Kingdom of Bahrain has reported more than 696,000 cases of coronavirus disease 2019 (COVID-19) and 1548 associated deaths as of December 26, 2022. Objectives: To better inform responses to future public health threats, this narrative review documents the challenges and responses to the COVID-19 pandemic in the Kingdom of Bahrain. Methods: A PubMed search was conducted focusing on severe acute respiratory syndrome or COVID-19 in Bahrain. Additional relevant references were also included from the authors' personal reference collections. Results: The search indicated that Bahrain achieved well-established control of the pandemic through robust public health measures, including an early, comprehensive vaccination program. Bahrain was among the first countries to grant emergency authorization for COVID-19 vaccines; as of December 2022, nearly 73% of the eligible population has been fully vaccinated, and approximately 60% has been boosted. Low case rates in recent months highlight Bahrain's successful response to the COVID-19 pandemic. Conclusions: Early organization, robust and systematic protective measures, and a comprehensive vaccination program were key components of the Kingdom's response to the pandemic; traveler quarantines and attempts to combat misinformation were of little or no benefit. These lessons provide guidance for future preparedness to minimize the public health impacts of another pandemic. (Curr Ther Res Clin Exp. 2024; XX:XXX-XXX).